Chinese voices behind ‘The Great Firewall’ - Rose Scarfe-James (Groundings, 2013)
The advent of the digital revolution has brought about a change in the nature of political engagement in China. The Internet and digital technologies have broadened the horizons of China’s net citizens and despite rigorous censorship and intervention on the part of the Chinese Communist Party (CCP); voices are being heard from behind the ‘Great Firewall’. With more than 500 million Internet users, Chinese citizens are a huge online presence, consequences of which include an explosion in blogging culture, cyber vigilantism and user-generated media content. It is clear that the Internet has empowered Chinese citizens in both the online and offline spheres. These developments have prompted scholars to contemplate whether there is a form of civil society developing in China in the wake of the digital revolution. However a culturally attuned conception of civil society must be developed in order to discuss an emerging Chinese civil society with any meaningful outcomes.